Pembuatan Pupuk Organik Cair Bonggol Pisang Untuk Mendukung Sistem Pertanian Organik Di Lembang Burasia, Kecamatan Bittuang, Kabupaten Tana Toraja - Agtasya Vivin Parantean; Crecentia Priskila; Febrianti Tandi; Selin Bessoran Palulun; Jens Batara Marewa (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2022)
Organic Waste Management and its utilization. The aim of organic waste management and the use of banana hump liquid organic fertilizer is to reduce agricultural waste and increase its benefits in the agricultural cycle for the community in Lembang Burasia. With this program, the community can find out how to make liquid organic fertilizer by utilizing waste and materials found around the community. These activities include (1) socializing the use of banana weevils to become POC; (2) Training on how to make POC from banana tubers; (3) making banana tubers into POC; (4) application of the use of banana weevils as POC. This activity can run well in accordance with the planning and objectives of the activity. The implementation of this activity received support from both the head of Lembang and local residents, which was indicated by their involvement in implementing the activity. The results of this activity have also provided special skills for local residents who have been directly involved in the process of making banana weevil POC.